2022
DOI: 10.31832/smj.1128439
|View full text |Cite
|
Sign up to set email alerts
|

300 million Patient Examinations per year; Evaluation of Emergency and Polyclinic Services of 2nd and 3rd Stage Public Health Facilities in Turkey

Abstract: Background: There are many applications to both emergency services and polyclinics in Turkey. Emergency services are the diagnosis and treatment units that meet a significant part of the patient population in Turkey. In our study, the number of patients admitted to and examined in our country's emergency services and hospital outpatient clinics, and the number of consultations requested during the diagnosis and treatment process were examined. The aim is to identify the applications to public hospitals in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…One-third of the annual outpatient clinic examinations in Turkey are performed in the ED, and all possible problems of the patients are attempted to be solved in the ED, and this situation prolongs the waiting time. 21 The length of these periods is due to the fact that this understanding continues even in extraordinary situations such as earthquakes for patients who will be hospitalized, and for patients who will be discharged, patients stay in EDs for a long time due to problems such as housing and lack of access to social support to receive follow-up treatment. Furthermore, patients requiring early interventions other than surgery, such as hemodialysis, received this treatment first and were re-examined for other injuries once the life-threatening situation had passed.…”
Section: Discussionmentioning
confidence: 99%
“…One-third of the annual outpatient clinic examinations in Turkey are performed in the ED, and all possible problems of the patients are attempted to be solved in the ED, and this situation prolongs the waiting time. 21 The length of these periods is due to the fact that this understanding continues even in extraordinary situations such as earthquakes for patients who will be hospitalized, and for patients who will be discharged, patients stay in EDs for a long time due to problems such as housing and lack of access to social support to receive follow-up treatment. Furthermore, patients requiring early interventions other than surgery, such as hemodialysis, received this treatment first and were re-examined for other injuries once the life-threatening situation had passed.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that, in Türkiye, the number of people seeking care at EDs in a year is nearly twice the country's population. 4 Studies from various countries have shown that EDs operate at capacities ranging from 50% to 68%. 5 One significant cause of ED overcrowding is the insufficient bed capacity in inpatient units and the extended lengths of stay for patients in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…In the last five years covering the period 2017–2021, this percentage has been observed to be 31.90% 32.60%, 40.30%, 45.40%, and 48.60% respectively in Turkey. 2 …”
Section: Introductionmentioning
confidence: 99%